Stock market integration between the Philippines and its major trading partners - Lai,, Yie Fung. (Universiti Malaysia Sarawak (UNIMAS), 2011)
This paper examines the stock integration and short run dynamic linkages between the Philippines and its major trading partners (Japan, CHina, Singapore and US) by using weekly data spanning from January 2000 to December 2009. This study uses Johansem and Juselius cointegration test (JJ), Victor Error Correction Model Granger causality test (VECM) and generalized impulse response functions (IRFs).